1985
DOI: 10.1037/h0080120
|View full text |Cite
|
Sign up to set email alerts
|

Role of peripheral vision in the directional control of rapid aiming movements.

Abstract: This study addresses the question of whether peripheral vision is involved in the control of hand trajectory direction during an aiming task performed at high speed. Ten adult subjects were required to aim at targets in various positions by making a punching movement with their hand. The experimental conditions were varied so that different parts of hand trajectory could be seen in the peripheral field. Two movement times were applied: < 130 msec, and 250-300 msec. The results indicate that a directional corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
54
0
6

Year Published

1986
1986
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(70 citation statements)
references
References 16 publications
(19 reference statements)
10
54
0
6
Order By: Relevance
“…This latter finding suggests that visual regulation of the limb is not confined to the homing phase of the movement as Woodworth's (1899) and Meyer et al's (1988) two-component models of speed-accuracy relations propose. Rather, visual control is also possible early in the limb trajectory (e.g., Bard, Hay & Fleury, 1985;Elliott, Carson, Goodman & Chua, 1991;Proteau, Roujoula & Messier, 2009;Saunders & Knill, 2004). In our recent multiple process model of speed-accuracy relations, we have termed this impulse control .…”
Section: Vertical Aiming 18mentioning
confidence: 99%
“…This latter finding suggests that visual regulation of the limb is not confined to the homing phase of the movement as Woodworth's (1899) and Meyer et al's (1988) two-component models of speed-accuracy relations propose. Rather, visual control is also possible early in the limb trajectory (e.g., Bard, Hay & Fleury, 1985;Elliott, Carson, Goodman & Chua, 1991;Proteau, Roujoula & Messier, 2009;Saunders & Knill, 2004). In our recent multiple process model of speed-accuracy relations, we have termed this impulse control .…”
Section: Vertical Aiming 18mentioning
confidence: 99%
“…Estimates of visual processing time ranged from 140 ms (Elliott & Allard, 1985) to less than 110 ms (Bard, Hay, & Fleury, 1985;Zelaznik, Hawkins, & Kisselbu-1 Target undershooting occurs to an even greater extent when visual feedback is eliminated or degraded during movement execution (e.g., Elliott & Lee, 1995). Surprisingly, even in tasks like foul and jump shot shooting in basketball, where overshoot errors are preferable to undershoot errors (i.e., because of the backboard), skilled performers tend to undershoot the target to a greater extent when vision of the target and limbs is degraded during execution (Ferraz de Oliveira, Huys, Oudejans, van de Langenberg, & Beek, 2007;Ferraz de Oliveira, Oudejans, & Beek, 2006).…”
Section: Early Online Controlmentioning
confidence: 99%
“…For example, Bard et al (1985) reported that rapid punching movements executed to move through target positions in left and right space could be corrected in as little as 110 ms. In keeping with the notion that the modulation of limb direction occurs early in the trajectory, Bard et al found that vision of the first 50% of the movement was more important than vision of the last 50% (see also Hansen, Cullen, & Elliott, 2005).…”
mentioning
confidence: 99%
“…When the movements are made in 3-D space (e.g., Khan et al, 2002), the general procedure has been to use resultant kinematic markers as reference points, but to separately examine spatial variability in the primary direction of the movement (i.e., amplitude variability) and perpendicular to the primary direction of the movement (i.e., directional variability). This approach was taken because these two movement dimensions may be controlled separately (see, e.g., Bard, Hay, & Fleury, 1985;Elliott et al, 2001;Ghez, Gordon, Ghilardi, & Sainburg, 1995). Thus, our analysis consisted of a 2 (vision condition) 4 (kinematic marker: PA, PV, PD, End) repeated measures ANOVA on the standard deviations associated with movement amplitude and those associated with left-right directional position.…”
Section: Discontinuities In the Trajectory And Their Effectivenessmentioning
confidence: 99%